Kajian Ragam dan Periode Penyimpanan Kombinasi Air Rebusan Daun Sirih dan Kayu Siwak Terhadap Pertumbuhan Streptococcus mutans - Yustin Nur Khoiriyah; Sri Murwaningsih (Biogenesis: Jurnal Ilmiah Biologi, 2017)
The community for maintaining healthy teeth and mouth has used betel and siwak wood plants. However, the benefits of a combination of both plants have not been widely known. The main output of this research was to know the utilization of a combination of betel leaf water and siwak wood as a mouthwash candidate. Combination of boiled water of both plants is a processed product, which has a shelf life. As a mouthwash product that is stored for a long time allegedly decreased the level of usefulness. One parameter of usability level to be observed in this study was the inhibition of Streptococcus mutans, the bacteria that cause dental caries. This study was laboratory experimental research, and use post test only with control group design with Cross-Sectional approach. Data analyzed by T-test and ANOVA followed by LSD test. Inhibition zone of boiled water stored at room temperature was smaller than cold temperature. However, T-test results showed that the diameter of inhibition zone of boiled water stored at room temperature and the cold temperature was not significantly different (p-value = 0,586> 0,05). Significantly decreased drag zone diameters occurred in a combination of boiled water stored for 16 and 18 days. Then the storage variety did not have a real effect, while the storage period significantly affects the inhibition power of boiled water in the growth of Streptococcus mutans.